2021
DOI: 10.3390/ijerph18168545
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, Practices and Viewpoints of Undergraduate University Students towards Self-Medication: An Institution-Based Study in Riyadh

Abstract: Rational and responsible self-medication (SM) is not only the key to better health outcomes, but also key to limiting adverse drug events. This institution-based cross-sectional study utilized seven- and four-item scales to assess the knowledge and attitude towards SM. Similarly, SM practices were measured using eight scale questions consisting of SM practice during the last six months, type of drug consumed, reason and frequency of SM, and so on. Statistical analyses were performed using SPSS. Overall, 371 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 24 publications
2
14
1
1
Order By: Relevance
“…These findings are in line with previous studies. 13,19,23,26,28,30 In the present study, about half of the students (42.9%) reported that they had practiced SM one to three times during the last six months, which is less than once a month. This is comparable with findings from students of AlMaarefa University, Riyadh.…”
Section: Discussionmentioning
confidence: 46%
See 4 more Smart Citations
“…These findings are in line with previous studies. 13,19,23,26,28,30 In the present study, about half of the students (42.9%) reported that they had practiced SM one to three times during the last six months, which is less than once a month. This is comparable with findings from students of AlMaarefa University, Riyadh.…”
Section: Discussionmentioning
confidence: 46%
“…In our study, we observed that 60% of medical students had practiced SM during the last six months, which is lower compared to findings in students from King Khalid University, Abha (98.7%), 23 AlQassim University (86.6%), 24 and Jazan University (87%), 21 Bangladeshi undergraduate pharmacy students (88%), 13 and students from Zabol University of Medical Sciences, Iran (57%), 26 and Kasturba Medical College, India (78.6%). 12 In contrast, students from AlMaarefa University, Riyadh (55%), 19 and Imam Abdulrahman Bin Faisal University (26%) in Dammam, Saudi Arabia, 20 demonstrated a lower prevalence of SM. We noticed that area of residence, marital status, father's profession, and distance to a healthcare facility had a significant impact on the practice of SM; similar findings were noted among AlMaarefa students, 19 where SM practice was low among students whose parents/family members were working in the health sector.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations